Determining the structure and evaluating the role of technical-tactical elements in basic table tennis playing systems - Munivrana, G.; Furjan-Mandic, G.; Kondric, M. (International Journal of Sports Science and Coaching, 2015)
A method of collecting data was developed in order to establish the overall structure of technical-tactical elements in table tennis and to evaluate their role in basic playing systems. For this purpose, a measuring instrument (a questionnaire) was formulated in order to collect the large quantity of empirical expert knowledge of eight top class table tennis trainers. On the basis of analysis of the experts` scores, the hierarchical structure of the technical-tactical elements in table tennis was obtained, which showed that the whole group of technical-tactical elements forming the table tennis technique can be divided into three basic groups: a group of technical-tactical elements (A) used in the phase of preparing one`s own and disabling the opponent`s attack; a group of technical-tactical elements (B) used in the phase of attack and counterattack; and a group of technical-tactical elements (C) used in the phase of defence. The relations between the obtained groups of technical-tactical elements and their role in three basic playing systems (Attack in the table zone, Attack from a half distance, Defence) were analysed by comparing the average values of the expert`s scores.